Antitumor screening of crude extracts of ten medicinal plants of Polygala genus from Southern Brazil - Tiago Tizziani, Dalila Venzke, Ana Paula Ruani, Lucas Bonfim Marques, Pedro Henrique Dias Moura Prazeres, Elaine Maria Souza-Fagundes, Moacir Geraldo Pizzolatti, Inês Maria Costa Brighente (Journal of Applied Pharmaceutical Science, 2017)
In this study crude extracts from 10 species among of the 39 Polygala L. genus found in the South region of Brazil, were subjected to screening for antitumor activity against the tumor cell lines, HL-60 (myeloid leukemia), Jurkat (lymphoblastic leukemia), THP-1 (monocytic leukemia), MCF-7 and MDA-MB-231 (breast carcinoma), HCT-116 (colorectal carcinoma) and Vero (kidney of green monkey, used as a non-tumor cell model). The evaluation was carried out using the MTT assay. Only the extracts of Polygala densiracemosa, Polygala campestris and Polygala molluginifolia inhibited the tumor cell viability by more than 50%. The best results were observed for P. molluginifolia, with inhibition of the cell viability of HL-60 (83%), Jurkat (78%), MDA-MB-231 (75%), MCF-7 (70%) and HCT-116 (64%), however this species also inhibited the viability of the Vero cells (32%). The P. campestris species showed selectivity for Jurkat (66%) and HL-60 (78%) cells whilst P. densiracemosa showed selectivity only for HL-60 cells (66%). In addition, the toxicity toward non-tumor cells was low (11% for P. campestris and 12% P. densiracemosa), showing that these species are promising sources for obtaining candidates for chemotherapy drugs.
Keywords: Polygala, Polygalaceae, antitumor screening, tumor cell.